A hidden mesencephalic variant of central pain. (2nd June 2020) - Convers, Philippe; Creac'h, Christelle; Beschet, Albert; Laurent, Bernard; Garcia‐Larrea, Luis; Peyron, Roland
Abstract: Background: Central post‐stroke pain (CPSP) can arise after lesions anywhere in the central somatosensory pathways, essentially within the spinothalamic system (STS). Although the STS can be selectively injured in the mesencephalon, CPSP has not been described in pure midbrain infarcts. Methods: Of more than 300 CPSP consecutive cases, we describe five patients who developed definite neuropathic pain following lesions circumscribed to the postero‐lateral mesencephalon. Results: The mesencephalic lesion responsible for pain was always haemorrhagic and always involved the spinothalamic tract (STT), as demonstrated by suppressed laser‐evoked potentials in every case, with or without preserved lemniscal function. In three cases the midbrain injury could be ascribed to trauma, presumably from the cerebellar tentorium. As a result of the paucity of sensory symptoms, the pain was considered as 'psychogenic' in two of the patients until electrophysiological testing confirmed STT involvement. Conclusion: Postero‐lateral midbrain lesions should be added to potential causes of CPSP. Because pain and spinothalamic deficits may be the only clinical sign, and because small lateral midbrain lesions may be difficult to trail with MRI, mesencephalic CPSP can be misdiagnosed as malingering or psychogenic pain for years. Significance: Selective spinothalamic injury caused by small lateral midbrain lesions is a very rare cause of central post‐stroke pain that can remain undiagnosed for years. It appears to obey to haemorrhagic, sometimes post‐traumatic lesions. Sudden development of contralateral burning pain with isolated spinothalamic deficits may be the only localizing sign, which can be easily objectively detected with electrophysiological testing.